Remarks on Null Geodesics of Born-Infeld Black Holes. (16th August 2012) - Fernando, Sharmanthie
Abstract : We present interesting properties of null geodesics of static charged black holes in Einstein-Born-Infeld gravity. These null geodesics represents the path for gravitons. In addition, we also study the path of photons for the Born-Infeld black hole which are null geodesics of an effective geometry. We will present how the bending of light is effected by the non-linear parameter β of the theory. Some other properties, such as the horizon radius and the temperature are also discussed in the context of the nonlinear parameter β .